Modern approaches to optimizing human resources policy in private medical organizations ("Journal "U". Economy. Management. Finance.", 2025)
The article discusses current issues of improving human resources policy in private medical organizations. The theoretical foundations and modern approaches to managing medical personnel are analyzed, and key problems in the field of human resources policy in private clinics are identified. Based on the conducted research, methodological recommendations have been developed for creating an effective system of personnel motivation and development, implementing modern personnel management technologies, and optimizing the processes of recruiting and adapting medical workers. Special attention has been paid to creating a corporate culture and ensuring comfort.
Keywords: personnel policy; private medical organizations; personnel management; motivation of medical workers; professional development; corporate culture; management efficiency; healthcare; HR technologies; and staff adaptation system